Central bank digital currencies consulting project the launch of the digital Euro - underlying technologiesa and real-world implementations - Salgueiro, Diogo José Carriço Monteiro (2022)
Financial innovations are often a consequence of technological advancements. The following Work Project aims at identifying how a wider adoption of digitalisation and technologies, such as Digital Ledger Technology (DLT), have led to new financial products that have affected consumers’ demand. Additionally, the report addresses the monetary authorities’ response in the form of Central Bank Digital Currency (CBDC), as, across the globe, Central Banks have launched several initiatives to study and launch CBDC’s. Finally, the thesis takes on a Euro-centric approach, focusing on the potential chosen technology and impacts a digital Euro can bring about.